Early predictors of cardiac dysfunction in Egyptian children with chronic kidney disease - Mohamed Abdelaziz El-Gamasy; Walid Ahmed El-Shehaby; Maaly M Mabrouk (Wolters Kluwer Medknow Publications, 2019)
Background: Cardiovascular morbidity (CVM) is the main etiology of mortality in children and adolescents with chronic kidney disease (CKD). CKD associated cardiovascular mortality is more common in children with diastolic cardiac dysfunction which was considered as an early indicator for death, while increased left ventricular mass (LVM) is a strong independent risk factor for these patients. Vitamin D deficiency was previously studied as one of the risk factors for CVM. Aim: The aim of the work was to investigate the relationship between biomarkers of mineral bone disorder including serum 25(OH) Vitamin D3 (25-OH D3), phosphorus and calcium × phosphorus (Ca×Po4) product with diastolic cardiac function and LVM in children and adolescents with CKD. Subjects and Methods: This was a cross-sectional observational study. Participants were classified into two groups: Group I including 86 pediatric patients with CKD (stages 4 or 5) and Group II including 40 healthy controls. Group I was subdivided into IA included children with diastolic dysfunction and IB included cases without diastolic dysfunction. 25-OH D3 level was measured by enhanced chemiluminescence method and intact parathyroid hormone (iPTH) by electrochemiluminescence method. Parameters for diastolic function and LVM were assessed by Doppler echocardiography, tissue Doppler imaging, and M-mode echocardiography. Results: 25-OH D3 level was significantly lower in Group I when compared to Group II. Diastolic dysfunction was present in 48.8% of the studied patients and was significantly associated with increased serum phosphorus and calcium-phosphorus product but not with decreased level of 25-OH D3. There was a significant positive correlation between LVM and iPTH. Conclusions: Hyperphosphatemia and high Ca×Po4 product were considered of prognostic value as they predict early diastolic dysfunction and increased LVM in children with CKD.